Pengembangan Modul Pembangkit Listrik Tenaga Surya untuk Mendukung Praktikum Siswa pada Mata Pelajaran Perangkat Pembangkit Kelas XI Kompetensi Keahlian Teknik Pembangkit Tenaga Listrik di SMK - Chusna, Chufadatul; Wibawanto, Slamet; Mahandi, Yogi Dwi (Universitas Pamulang, Prodi teknik Elektro, 2024)
The teaching material is an important element in the learning process because it has a variety of crucial functions. First, the material allows the student to learn independently without the presence of a teacher or a friend. Second, the student can study anywhere and at any time according to their wishes. Third, it helps the student become an independent learner. Lastly, it serves as a guide that guides the student's learning activity. As a result of interviews with instructors in the field of Electrical Equipment, it is known that the material module of the Solar Power Plant does not support learning. Therefore, the aim of this study is to create a learning module about electrical devices that can be used as a learning support in the classroom for students in class XI of Electric Power Plant Engineering at SMK. Using the 4D model (Define, Design, Develop, and Disseminate), this is a development module that has four chapters: solar energy, general PLTS descriptions, components, and PLTS operations. The results of the study showed that the generator learning module created was highly valid, with an average of 93.40% of all tests. Validity of expert 1 reached 95.07% with highly valid category, validity of specialist 2 reached 95.83%, and validity test of small and large groups reached 89.22% with very valid categories, respectively.